In vitro evaluation of force-expansion characteristics in a newly designed orthodontic expansion screw compared to conventional screws - Oshagh Morteza; Momeni Danaei S; Hematian M; Oshagh M; Zade A; Saboori A (Wolters Kluwer Medknow Publications, 2009)
Objective : Expansion screws like Hyrax, Haas and other types, produce heavy interrupted forces which are unfavorable for dental movement and could be harmful to the tooth and periodontium. The other disadvantage of these screws is the need for patient cooperation for their regular activation. The purpose of this study was to design a screw and compare its force- expansion curve with other types. Materials and Methods : A new screw was designed and fabricated in the same dimension, with conventional types, with the ability of 8 mm expansion (Free wire length: 12 mm, initial compression: 4.5 mm, spring wire diameter: 0.4 mm, spring diameter: 3 mm, number of the coils: n0 ine, material: s0 tainless steel). In this in vitro study, the new screw was placed in an acrylic orthodontic appliance, and after mounting on a stone cast, the force-expansion curve was evaluated by a compression test machine and compared to other screws. Results : Force-expansion curve of designed screw had a flatter inclination compared to other screws. Generally it produced a light continuous force (two to 3.5 pounds) for every 4 mm of expansion. Conclusion : In comparison with heavy and interrupted forces of other screws, the newly designed screw created light and continuous forces.